Dorling Kindersley concise atlas of the world (Dorling Kindersley Pub., 2005)
From the defining boundaries of the Balkan states to the icy terrain of Antartica, this is the definitive reference atlas of the world today. Over 400 digital maps provide an outstanding overview of the physical, political, economic and demographic geography of the world.